The Effect of Leadership, Motivation, and Work Environment on Employee Performance at PT. BJA Sidoarjo: Pengaruh Kepemimpinan, Motivasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. BJA Sidoarjo - Ani Maslacha Syaiful Bakhri; As'at Rizal (Academia Open, 2021)
This study aims to determine the effect of leadership, motivation, and work environment on employee performance at PT. BJA Sidoarjo. This research includes quantitative research with hypothesis testing. The sample used in this study were 101 employees at PT. BJA Sidoarjo. The analytical tools used in this research are multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classical assumption test using SPSS. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The result of this research is that there is a simultaneous influence of leadership, motivation and work environment on employee performance. Partially, the variables of leadership, motivation and work environment have an influence on employee performance. and the work environment variable is the variable that has the most significant effect on employee performance.